2019
DOI: 10.3389/fchem.2019.00251
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Density Analysis of Cellulose Thin Films

Abstract: An approach for the multilayer density analysis of polysaccharide thin films at the example of cellulose is presented. In detail, a model was developed for the evaluation of the density in different layers across the thickness direction of the film. The cellulose thin film was split into a so called “roughness layer” present at the surface and a “bulk layer” attached to the substrate surface. For this approach, a combination of multi-parameter surface plasmon resonance spectroscopy (SPR) and atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…All SPR measurements were performed at 20 °C under the constant flow of 100 µL min −1 . The thickness of the adsorbed layer was determined with Equation () [ 56 ] d =ld2 Δanglemnan0 where d is the thickness, l d is the characteristic evanescent electromagnetic field decay length (estimated as 0.37 of the light wavelength 670 nm), Δ angle is the change in the SPR angle, m is the sensitivity factor for the sensor (109.94° RIU −1 , obtained after calibration), n 0 is the refractive index of the bulk solution (1.334 RIU), and n a is the refractive index of the adsorbed substance (for NPcat 1.410 [ 57 ] ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All SPR measurements were performed at 20 °C under the constant flow of 100 µL min −1 . The thickness of the adsorbed layer was determined with Equation () [ 56 ] d =ld2 Δanglemnan0 where d is the thickness, l d is the characteristic evanescent electromagnetic field decay length (estimated as 0.37 of the light wavelength 670 nm), Δ angle is the change in the SPR angle, m is the sensitivity factor for the sensor (109.94° RIU −1 , obtained after calibration), n 0 is the refractive index of the bulk solution (1.334 RIU), and n a is the refractive index of the adsorbed substance (for NPcat 1.410 [ 57 ] ).…”
Section: Methodsmentioning
confidence: 99%
“…The mass of the adsorbed layer per unit area was determined with Equation () [ 58 ] Δm = d×ρ where Δ m is the adsorbed mass, d is the thickness, and ρ is the packing density of the NPcat (estimated to be 1.39 g cm −3[ 57 ] ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle also the density can be determined at the interfaces. Sampl et al (2019) showed that the outermost layer of cellulose thin films (3 nm) has a different refractive index and density than the bulk film. Combining SPR with QCM-D, swelling studies can be performed that allow the monitoring of water uptake inside different biopolymer thin films (Kontturi et al, 2013).…”
Section: Surface Plasmon Resonance Spectroscopymentioning
confidence: 99%